De la « rurbanisation » du héros américain : The Rise of Silas Lapham - Guillaume TANGUY (E-REA)
The bipolar representation of the city (the celestial city vs. Babylon the great) is a distinguishing feature of the American psyche. A similar ambivalence can be traced in the ideological conflict between two types of discourse, one pastoral and one mercantilist, the former celebrating the “garden” as opposed to the “machine” (to use the terms of Leo Marx), the latter advocating the quest for the utopian city. The question of the city, which is recurrent in the novels of W.D. Howells, is at the core of The Rise of Silas Lapham. But can the protagonist’s final decision to return to his “native hills” in Vermont substantiate a “pastoral” reading of the novel? Insofar as Silas returns to Vermont in order to exploit nature on an industrial (if more modest) scale, his decision is linked to a process of “rurbanization” – an attempt to tame the landscape – which appears as the exact fulfilment of the prophetic vision articulated by Charles Wilson Peale in The Exhumation of the Mastodon (1806). Specifically, the symbolic potential of two key episodes – the discovery of the paint mine and the digging of the foundations of Silas’s house on Beacon Street – is indicative of this civilizing paradigm. The city, according to Howells, is America’s ultimate destiny.